Respuesta :

Answer:

Converting the equation [tex]x^2-20x+13=0[/tex] into completing the square method we get: [tex]\mathbf{(x-10)^2=87}[/tex]

Step-by-step explanation:

we are given quadratic equation: [tex]x^2-20x+13=0[/tex]

And we need to convert it into completing the square method.

Completing the square method is of form: [tex]a^2-2ab+b^2=(a-b)^2[/tex]

Looking at the given equation [tex]x^2-20x+13=0[/tex]

We have a = x

then we have middle term 20x that can be written in form of 2ab So, we have a=x and b=? Multiplying 10 with 2 we get 20 so, we can say that b = 20

So, 20x in form of 2ab can be written as:  2(x)(10)

So, we need to add and subtract (10)^2 on both sides

[tex]x^2-20x+13=0\\x^2-2(x)(10)+(10)^2-(10)^2+13=0\\(x^2-2(x)(10)+(10)^2) \:can\: be\: written\: as\: (x-10)^2 \\(x-10)^2-100+13=0\\(x-10)^2-87=0\\(x-10)^2=87[/tex]

So, converting the equation [tex]x^2-20x+13=0[/tex] into completing the square method we get: [tex]\mathbf{(x-10)^2=87}[/tex]